PEMERIKSAAN KADAR YODIUM DAN PENYULUHAN GANGGUAN AKIBAT KEKURANGAN YODIUM (GAKY) PADA ANAK USIA SEKOLAH - Maratni, N.P.T.; Wihandani, D.M.; Ruma, I.M.W.; Surudarma, I.W.; Putri, P.M.W.S.; Artawan, I.W.T.R. (Buletin Udayana Mengabdi, 2025)
Iodine deficiency disorders (IDD) are closely related to mental and intelligence development disorders. Iodine intake can decrease in people who live in mountainous areas. Geographically, the location of Songan B Village is in the mountains and far from the lowlands so that disruption to the supply of iodized salt can occur. Implementation of community service activities is carried out for 8 months (April-December 2024) which is divided into three stages, namely the preparation stage, checking iodine levels and counseling on IDD. Of the 83 people who took part in this service activity, the majority were girls, namely 43 people (51.8%) with an average age of 12.53 ± 0.503 years. The average weight of children who participated in this service activity was 39.45  ±  7.336 kg and the average height of children was 147  ±  15.011 cm. Iodine level checks were carried out at the first visit. The average urine iodine level in school-age children in Songan B Village was 194.94  ±  135.68 so it was still within the normal range. Most of the children in Songan B Village, namely 62 people (74.7%) had normal urine iodine levels. Only 16 people (19.3%) had mild iodine deficiency, 3 people (3.6%) had moderate iodine deficiency, and 2 people (2.4%) had severe iodine deficiency. IDD counseling activities were carried out on the second visit. All children have received health education regarding IDD. Children who experience moderate and severe iodine deficiency are given more intensive education, apart from increasing their consumption of foods rich in iodine, they are also advised to consult further with a pediatrician and clinical nutritionist so they can receive further treatment.